Analisis Keamanan Lalu Lintas Paket Data Pada Ubuntu Menggunakan Metode Attack Centric - Feizil Afrizal; Rometdo Muzawi; Yoyon Efendi (Ikatan Ahli Informatika Indonesia (IAII), 2017)
Data traffic security in a network is very important, especially on a large scale such as companies, agencies and universities that have a lot of personal data. Effective data security is required, effective, flexible, not consuming enough time, big expense and have good advantages and shortcomings that are not too big so that data is not easy to be manipulated, analyzed, and attacked by irresponsible party. In the security analysis of data traffic on the ubuntu operating system is using Attack Centric method where each security attack will be analyzed its characteristics, after analyzing these characteristics then in the security mechanism for defense. This study aims to produce a system for analyzing, documenting attacks and how to handle it simply, in the hope that this analysis results, can reduce crime in the virtual world, to users who are not very proficient in cyberspace, and increase knowledge for users of the Internet network